2021
DOI: 10.1108/dlp-03-2021-0022
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of core technology competencies for systems librarian

Abstract: Purpose This study aimed to develop and validate a list of core technology competencies for systems librarian in Pakistan. Design/methodology/approach Survey method was used to conduct this investigation. A structured questionnaire, consisting of 52 competency statements categorized into six core technology areas, was developed based on an extensive literature review, experts’ scrutiny and pilot testing. The administration of the survey questionnaire was done though online environments such as related listse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 24 publications
(51 reference statements)
1
3
0
Order By: Relevance
“…A previous study also confirmed that library automation and adoption of library software plays a vital role in the effectiveness of library use (Ukachi et al , 2014). These findings also relate with the previous study of Naveed et al (2021) that indicated that because of the availability of necessary library software modules and the potential for modification, the majority of libraries were satisfied with LIMS free-based software and KOHA OSS. Another previous study also confirmed that due of its free availability, MARC21 cataloguing standards support and online public access catalogue (OPAC) functionality, Koha was accepted by librarians (Asim and Mairaj, 2019).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…A previous study also confirmed that library automation and adoption of library software plays a vital role in the effectiveness of library use (Ukachi et al , 2014). These findings also relate with the previous study of Naveed et al (2021) that indicated that because of the availability of necessary library software modules and the potential for modification, the majority of libraries were satisfied with LIMS free-based software and KOHA OSS. Another previous study also confirmed that due of its free availability, MARC21 cataloguing standards support and online public access catalogue (OPAC) functionality, Koha was accepted by librarians (Asim and Mairaj, 2019).…”
Section: Discussionsupporting
confidence: 86%
“…In the province of Punjab, he noticed that 22 universities/degree-awarding institutions (DAIs) were using Koha ILS. Naveed et al (2021) presented an analysis that examines the present state of the library automation systems being used within the Lahore libraries. They observed that 33 recognized universities and DAI libraries of the Higher Education Commission (HEC) used a library management system in Lahore and most librarians were comfortable with integrated library management system (ILMS) free-based software and with Koha OSS.…”
Section: Literature Reviewmentioning
confidence: 99%
“…, 2018). Personal competency is the set of skills, attitudes, and values that enable librarians to work effectively and efficiently, to demonstrate the added value of their contributions, and to survive in the new world of work (Naveed et al. , 2021).…”
Section: Discussionmentioning
confidence: 99%
“…However, researchers have claimed that information technology is largely associated with teamwork, subjective motivation, and improved skills and training levels (Andrews et al, 2018). Personal competency is the set of skills, attitudes, and values that enable librarians to work effectively and efficiently, to demonstrate the added value of their contributions, and to survive in the new world of work (Naveed et al, 2021). These skills include a wide range of personal skills like critical thinking, social and communication skills, teamwork, and ethical attitudes.…”
Section: Technological Incentives In Communitiesmentioning
confidence: 99%